Factors related to nurses continuous professional development in hospitals: A scoping review - Maria Anita Sari; Ni Gusti Ayu Eka; Enjelica Putri Manalu; Erica Dorelia Pajuk; Keyla Friska Br Siraut (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Continuing Professional Development (CPD) is a key strategy to support lifelong learning and improve nursing practice. Despite its recognized importance, CPD implementation in hospital settings remains inconsistent and often faces various challenges. Understanding the factors that influence nurses’ participation in CPD is essential to enhance its effectiveness and sustainability. Purpose: To identify factors related to the continuing professional development of nurses in hospitals. Method: A scoping review using the PRISMA-ScR guidelines. A systematic search was conducted in PubMed, MEDLINE, and Science Direct for articles published between 2020 and 2025. A total of 16 studies were included, comprising quantitative, qualitative, and mixed-method designs. Thematic analysis was conducted to identify key themes. Results: Three main themes emerged: motivation and barriers to participation, CPD implementation and outcomes, and impact of working conditions. Internal motivation, financial incentives, and professional growth were key drivers, while fatigue, cost, and scheduling issues were major barriers. Nurses’ perceptions of CPD were shaped by training relevance, accessibility, and effectiveness. Workload, leadership support, and organizational culture significantly influenced engagement. Conclusion: CPD implementation among nurses is shaped by motivational factors, nurse’s perceptions conduct by CPD implementation and outcome, and workplace conditions. To enhance participation and effectiveness, healthcare institutions must adopt holistic strategies that address individual needs, ensure program relevance, and foster supportive environments.